On the average‐case complexity of Shellsort - Vitanyi, Paul (Random structures & algorithms, 2018)
We prove a lower bound expressed in the increment sequence on the average‐case complexity of the number of inversions of Shellsort. This lower bound is sharp in every case where it could be checked. A special case of this lower bound yields the general Jiang‐Li‐Vitányi lower bound. We obtain new results, for example, determining the average‐case complexity precisely in the Yao‐Janson‐Knuth 3‐pass case.